Effects of glutathione s-transferase (GST) M1 and T1 polymorphisms on antioxidant vitamins and oxidative stress-related parameters in Korean subclinical hypertensive subjects after kale juice (Brassica oleracea acephala) supplementation - Lee, Hye-Jin (Nutr Res Pract, 2018)
BACKGROUND/OBJECTIVES: Glutathione s-transferase (GST) is involved in the formation of a multigene family comprising phase II detoxification enzymes, involved in the detoxification of reactive oxygen species. This study evaluated whether daily supplementation with kale juice could modulate levels of plasma antioxidant vitamins and oxidative stress-related parameters. We further examined whether this modulation was affected by combined GSTM1 and T1 polymorphisms. SUBJECTS/METHODS: Totally, 84 subclinical hypertensive patients having systolic blood pressure (BP) over 130 mmHg or diastolic BP over 85 mmHg, received 300 mL of kale juice daily for 6 weeks. Blood samples were drawn before start of study and after completion of 6 weeks. RESULTS: After supplementation, we observed significant decrease in DNA damage and increase in erythrocyte catalase activity in all genotypes. Plasma level of vitamin C was significantly increased in the wild/null and double null genotypes. The plasma levels of β-carotene, erythrocyte glutathione peroxidase activity, and nitric oxide were increased only in the wild/null genotype after kale juice supplementation. CONCLUSIONS: The effect of kale juice was significantly greater in the GSTM1 null genotype and wild/null genotype groups, suggesting possibility of personalized nutritional prescriptions based on personal genetics.